Teacher’s Professional Self-Awareness Within The Interactions With Students In Higher Education: Temporality and Relationality - Žydžiūnaitė, Vilma; Daugėla, Marius (Acta Paedagogica Vilnensia, 2020)
Becoming and being a teacher in higher education is a long process of individual transformation. The research aims at highlighting the meaning of time and relations in regard to teachers’ professional self-awareness through their interactions with students in higher education. The research design was qualitative in which the phenomenological methodology according to Max van Manen version was applied. Findings revealed that temporality and relationality are social constructs that shape the teacher-student interactions in higher education as they are loaded with worldviews that guide their educational actions and and their relationships. Thus their subjectivities and life-world educational experiences-based worlds are built on temporalities. A higher education teacher’s professional self-awareness is a developmental process which requires from the person reflection on his/her own experiences. Teachers through interactions with students balance between expectations and requirements which encourage both sides to find ways of integrating creative methods into the teaching and learning processes. Through working with students, teachers step into the “unknown” and learn within togetherness. Being in togetherness brings bilateral interchange between teachers and students, which motivates both sides to be self-aware. These reciprocal interactions invite participants to grow and seek mutual interchange through different experiences and contexts.